2015
DOI: 10.1111/jcpt.12263
|View full text |Cite
|
Sign up to set email alerts
|

Association ofABCB1C3435T polymorphism with phenobarbital resistance in Thai patients with epilepsy

Abstract: Thai patients of ABCB1 3435CC genotype and with focal epilepsy were more often PB resistant. Those two factors partly account for the variability in Thai epilepsy patients' response to phenobarbital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…1 ). Only 13 met the inclusion criteria and constituted the data set for this analysis [ 22 29 , 31 , 33 36 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Only 13 met the inclusion criteria and constituted the data set for this analysis [ 22 29 , 31 , 33 36 ] (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The included studies were heterogeneous for the study characteristics. The analysis of data showed that 454 of 1653 AEDs-resistant patients (27.465%) and 282 of 1732 AEDs-responsive patients (16.282%) were included in the statistical analysis [ 22 29 , 31 , 33 36 ]. The frequency of AEDs-resistant cases was higher than AEDs-responsive patients.…”
Section: Resultsmentioning
confidence: 99%
“…C3435T in exon 26 (rs1045642) is the most extensively studied ABCB1 SNP [23]. A number of studies have reported the correlations among ABCB1 rs1045642 polymorphism and AED pharmacokinetics [8,24,25], but few studies were focused on OXC. In the present study, we showed that patients with epilepsy with the CC genotype of ABCB1 rs1045642 had a higher OXC concentration in comparison with CT and TT genotypes, suggesting patients with homozygous wild-type carriers required lower OXC maintenance dose to achieve the referenced effective plasma level.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, two meta-analyses of these studies revealed no significant association between resistance to AEDs and the C3435T genotype [33,35] . Most recent studies continue to provide evidence of significant associations between drug resistance and ABCB1 3435 genotypes [36] . In addition, the results of a recent meta-analysis indicates that ABCB1 C3435T polymorphism, especially TT genotype, plays an important role in refractory epilepsy; the authors suggest that genetic screening of this genotype, before starting the treatment, may be useful to predict AED response [37] .…”
Section: Pharmacoresistancementioning
confidence: 99%